Opinions and intentions of parents of an autistic child toward genetic research results: two typical profiles - Baret, Laurence (Nature Publishing Group, 2011)
Returning results to research participants is increasingly acknowledged in research ethics guidelines. But few research teams actually do it or provide mechanisms for offering it as an option. We explored the perspective of parents of an autistic child participating in genetic research. In all, 388 questionnaires were sent to 194 parents; 158 questionnaires were completed (89 mothers and 69 fathers), giving a response rate of 41%. 97% of respondents (n=153) fully expressed a strong desire to receive research results, either general or individual ones. The survey solicited parents' opinions as to what means could be put in place to return research results. The majority held the research team responsible for returning individual results (79.7%, n=126). They indicated that it should occur at the completion of the research project (69%, n=109), by mail (75.3%, n=119). Over three quarters felt the Ministry of Health should cover the associated costs (77.8%, n=123). If the communication of individual findings, whether positive or negative, were to be possible, these would allow some respondents ‘to be prepared for the future' (37%, n=57), without necessarily having practical benefits (21%, n=32), but at least bringing them ‘relief or understanding' (14%, n=21). Moreover, parents were clear about the difference between research and clinical settings. This study underlines the importance of broadening the discussion about the communication of research results, especially individual ones. We believe that the integration of different perspectives – those of researchers, clinicians, ethics committees and participants – will enrich the debate and offer enlightenment for future ethical guidelines.